The Effect of Educational Media in Increasing Pregnant Women's Knowledge of Flood Disaster Preparedness: Animated Video vs. Pocket Book - Larasati, Manggiasih; Trikusumawardani, Aiswara (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Flood disasters can threaten the health of pregnant women and disrupt access to healthcare services, increase the risk of diseases, and cause stress. Disaster preparedness is an important aspect that pregnant women must know and prepare for in the event of a flood. Therefore, education through animation videos and pocketbooks is needed to increase pregnant women's knowledge about flood disaster preparedness. This study uses a Quasi-Experiment “Pretest-Posttest Two Group Design” with two respondent groups: the animation video group and the pocketbook group. The data collection process was carried out from October to December 2024, by accidental sampling. This research involved 62 pregnant women respondents who undergo pregnancy check-ups at the Pondok Gede Health Center, and the data were analyzed using the Mann Whitney test. The results showed that the use of animation videos and pocketbooks had an effect on increasing pregnant women's knowledge about flood disaster preparedness (p-value 0.001). The knowledge of pregnant women about flood disaster preparedness using animation videos increased by 24.94%, while using the pocketbook increased by 38.06%. It can be concluded that the use of educational media, both animation videos and pocketbooks, equally influenced the improvement of pregnant women's knowledge about flood disaster preparedness. However, the use of pocketbooks is more effective in increasing pregnant women's knowledge about flood disaster preparedness compared to animation videos.